Characterization of Hybrid Sol-gel Coatings Applied over Tinplate - Álvarez,D. (2013)
The present work studies the behavior of hybrid sol-gel films based on tetraethyl orthosilicate (TEOS) and vinyltrimethylsiloxane (VTMS) precursors applied over commercial tinplate. In previous works VTMS films obtained by the sol-gel technology were tested to verify their good corrosion performance over short immersion times in a citric acid/sodium citrate buffer solution. However, at longer exposure times the high porosity inherent to organic sol-gel films allows the aggressive media to reach the metallic substrate and start the corrosion process. In order to overcome these limitations, hybrid organic-inorganic sol-gel coatings were obtained using the dip- coating method. This work also studies the influence of the ageing time of the hybrid sol-gel in the formation of a uniform and continuous film. The obtained layers were characterized using a Scanning Electron Microscopy (SEM) and mechanical profilometry. The corrosion performance in organic acid media was tested using polarization curves and Electrochemical Impedance Spectroscopy (EIS) with a 0.1M citric/citrate buffer solution as electrolyte. The results obtained suggest that a minimum ageing time of 10 days is needed to obtain uniform films. The electrochemical measurements indicate a clear improvement on the barrier properties on the hybrid sol-gel compared to the organic ones. A major decrease in the impedance values after 24 hours of immersion indicates that it is necessary to improve the long-term barrier properties to achieve an industrial application.